International Careers: U.S. Undergraduates’ Motivations and Concerns - Punteney, Katherine (Journal of International Students, 2016)
Despite the consensus among industry leaders, policymakers, educational institutions, and students themselves that it is essential that U.S. college graduates be prepared for international careers, little attention is given to understanding the dynamics that encourage or dissuade students from such a pursuit. A survey administered to U.S. undergraduates reveals that key factors motivating students include love of travel, interest in other cultures, the possibility of earning a high salary, and the potential for opportunities in the major discipline. Key concerns include leaving family and friends and a lack of foreign language ability. It is argued that the internationalization of career advising is vital and urgent and that administrators, international educators, career centers, and academic departments must all take purposeful action